Evolution of sinonasal clinical features in children with cystic fibrosis. (September 2019) - Suy, P.; Coudert, A.; Vrielynck, S.; Truy, E.; Hermann, R.; Ayari-Khalfallah, S.
Abstract: Objective: to assess the evolution of sinonasal manifestations in children with cystic fibrosis, since the improvement of their prognosis over the last decades. Methods: an observational, monocentric study with a retrospective cohort. We included 173 children (from 4 to 18 years old) with cystic fibrosis followed at the pediatric cystic fibrosis center of lyon, france. We collected respiratory, infectious and nutritional data, sinonasal complaints and physical examination at the onset of sinonasal symptoms (t-0), at the most severe of evolution (t-max) and at the end of followup (t-end). Results: sinonasal symptomatology appeared early around 5.4 years old, then rapidly reached the maximum at 6.9 years and finally improved during childhood (p < 0.0001), reaching scores at t-end significantly better than at t-0 (p < 0.0001). This evolution was significant for nasal obstruction, rhinorrhea and snoring. The other symptoms were rarer, with no significant 38, 7% at t-max (p < 0.0001), and 29, 5% at t-end (p = 0.52). The lildholdt score, turbinate hypertrophy and medial bulging of medial wall of the maxillary sinus followed the same evolution (p < 0.003). There was no association between sinonasal evolution and cystic fibrosis disease at infectious, respiratory or nutritional level. Conclusion: it is the only recent study evaluating the evolution of each sinonasal manifestations in children with cystic fibrosis. Rhinosinusitis improved during childhood, reaching better scores than at the beginning of management. This particular improvement may be related to good effectiveness to ent management, but also to a positive effect of nasal cavity growth, independently to extra-ent manifestations.